Immune Evasion, a Potential Mechanism of Trichothecenes: New Insights into Negative Immune Regulations - Wu, Qinghua; Wu, Wenda; Franca, Tanos C C; Jacevic, Vesna; Wang, Xu; Kuca, Kamil (International journal of molecular sciences, 2018)
Days ago, the Nobel Prize in Physiology or Medicine 2018 was awarded jointly to James P. Allison and Tasuku Honjo "for their discovery of cancer therapy by inhibition of negative immune regulation". This news has increased the attention on immunotoxicity and immune evasion mechanisms, which are once again hot research topics. Actually, increasing lines of evidence show that trichothecene mycotoxins have a strong immunosuppressive effect. These mycotoxins suppress the host immunity and make them more sensitive to the infection of pathogens, including bacteria and viruses. However, the underlying mechanism(s) in this context is still poorly understood. Interestingly, recent work showed that an immune evasion mechanism might be involved in trichothecene immunotoxicity. In this work, we discuss the potential immune evasion mechanism in trichothecene immunotoxicity. More importantly, under these circumstances, we are pleased to compile a Special Issue entitled "Biochemistry, Molecular Biology, and Toxicology of Natural and Synthetic Toxins" for the International Journal of Molecular Sciences (IJMS). Researchers are encouraged to share their latest interesting findings with the readers of IJMS.
Keywords: trichotheceny; immune evasion; immunotoxicity; Animals; T-2 toxin; Humans; trichothecenes; negative immune regulations; lidé; Trichothecenes; zvířata; Immunosuppressive Agents; Immune Evasion; imunosupresiva; imunitní únik